2022
DOI: 10.3390/ijms231911295
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Alpha-Crystallin to Cortical and Nuclear Lens Lipid Membranes Derived from a Single Lens

Abstract: Several studies reported that α-crystallin concentrations in the eye lens cytoplasm decrease with a corresponding increase in membrane-bound α-crystallin with age and cataracts. The influence of the lipid and cholesterol composition difference between cortical membrane (CM) and nuclear membrane (NM) on α-crystallin binding to membranes is still unclear. This study uses the electron paramagnetic resonance (EPR) spin-labeling method to investigate the α-crystallin binding to bovine CM and NM derived from the tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(27 citation statements)
references
References 133 publications
2
20
0
Order By: Relevance
“…Using continuous wave EPR spin labeling and SUVs as a membrane model, Mainali’s group showed that high Chol content and the presence of CBDs inhibits the binding of α-crystallin to membranes made of the major PLs of the eye lens fiber cell plasma membranes. They showed that the same conclusion is valid for membranes (SUV) made of the total lipids extracted from bovine cortical and nuclear lenses [ 97 ]. These results present another mechanism through which high Chol and CBDs protect the eye lens against age-related cataract development.…”
Section: Understanding Of Cbd Functions In Model Membranes Helps To U...mentioning
confidence: 87%
“…Using continuous wave EPR spin labeling and SUVs as a membrane model, Mainali’s group showed that high Chol content and the presence of CBDs inhibits the binding of α-crystallin to membranes made of the major PLs of the eye lens fiber cell plasma membranes. They showed that the same conclusion is valid for membranes (SUV) made of the total lipids extracted from bovine cortical and nuclear lenses [ 97 ]. These results present another mechanism through which high Chol and CBDs protect the eye lens against age-related cataract development.…”
Section: Understanding Of Cbd Functions In Model Membranes Helps To U...mentioning
confidence: 87%
“…Additional studies of α-crystallin in Chol-containing lipid membranes showed that both the membrane lipid and Chol composition strongly affects the membrane interactions of α-crystallin and the physical membrane properties [67,70]. Our most recent studies on α-crystallin interactions with isolated bovine lens cortical and nuclear total lipids showed α-crystallin binds to both the CM and NM but has significantly higher binding in the NM due to the variations in lipid and Chol composition between the lens regions [75]. Ultimately, these studies show α-crystallin binds to the lens lipid membrane and is strongly modulated by the lens membrane lipid and Chol composition.…”
Section: Introductionmentioning
confidence: 90%
“…Moreover, the 68 yo female donor with the highest MSO by α-crystallin in the CM was a long-term smoker, pre-diabetic, and had hypertension, which have all been associated with increasing oxidative stress and the development of cataracts [77][78][79][80][81][82][83][84][85][86]. As oxidative stress has been shown to likely reduce the lens Chol composition [35,[44][45][46][47][48], and reduced Chol is shown to lead to a diminished number and size of CBDs in CM and NM [43], the development of cataracts [50], and allow for increased α-crystallin binding [67,70,75], a reduction in Chol and CBDs content is likely why the highest MSO is seen in this donor. Therefore, in unison with gender-related risks, these health conditions will likely reduce the Chol and CBD content and allow for increased membrane binding with an increase in cataract grade.…”
Section: Mso By α-Crystallin In Individual Eye Lens Cortical and Nucl...mentioning
confidence: 99%
See 2 more Smart Citations